MODEL PEMBERDAYAAN KADER POSYANDU DALAM PROGRAM STUNTING DI KOTA BATU: (Studi Kasus pada Dinas Kesehatan Kota Batu Tahun 2018 - 2023) - Prabandari, Safira Lestari (Jurnal Administrasi Publik, 2024)
Posyandu cadre empowerment Model in Stunting Program in Batu City (Case Study in Batu City Health Office 2018-2023). The provision of stunting prevalence data through an accurate data collection system is very important in monitoring and evaluating efforts to accelerate stunting reduction at the National, district/city level, one of which is Batu City. The number of stunting cases in Batu City, East Java, is known to be relatively high. The Batu city government makes a target until the end of 2023, the stunting rate in the Batu City area can decrease and be at 10.8 percent (Batu City Government, 2023). Based on data from the Office of women's empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) of Batu City, when viewed from the 2018-2020 period, there is a decrease in stunting prevalence in the region. In that period, the prevalence rate of stunting in Batu city, which was recorded at 28.33 percent in 2018, decreased to 14.83 percent in 2020, and in the 2020-2022 period, the prevalence of stunting ranged from 14 percent. The purpose of this study was to explain and analyze the posyandu cadre empowerment model in the stunting program in Batu City in 2018-2023 and its inhibitors. The research method used is qualitative which aims to describe and analyze the model of posyandu cadre empowerment.